2018
DOI: 10.1039/c8ob01795f
|View full text |Cite
|
Sign up to set email alerts
|

Novel binaphthyl and biphenyl α- and β-amino acids and esters: organocatalysis of asymmetric Diels–Alder reactions. A combined synthetic and computational study

Abstract: Asymmetric catalysis of the Diels-Alder reaction between cyclopentadiene and cinnamaldehydes has been studied using as catalysts a range of novel α- and β-aminoacids and aminoesters with binaphthyl and biphenyl backbones, providing enantioselectivities of up to 62% ee. B3LYP/6-31G* calculations, including free energy corrections, have been carried out on a binaphthyl catalyst example to identify transition state structures and to aid in the identification of major enantiomers. The calculated product ratios agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 107 publications
1
4
0
Order By: Relevance
“…The dihydro-azepine monomer is formed by a nucleophilic substitution of the tetra-bromide compound 2 with the primary amine of choice. This route is similar to that previously reported [44].…”
Section: Synthesis Of the Chiral Azepine Building Blockssupporting
confidence: 92%
“…The dihydro-azepine monomer is formed by a nucleophilic substitution of the tetra-bromide compound 2 with the primary amine of choice. This route is similar to that previously reported [44].…”
Section: Synthesis Of the Chiral Azepine Building Blockssupporting
confidence: 92%
“…Biphenyl esters have been reported as important building blocks for the development of pharmaceuticals in diverse indication areas, and for use in a wide range of technical applications [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18]. In order to allow an inexpensive, environmentally friendly, and efficient access to biphenyl ester core moieties, we adopted a biomimetic iron(III)-catalyzed, solid-phase coupling reaction.…”
Section: Resultsmentioning
confidence: 99%
“…No study has yet been reported for the selective transformation of biphenyl-based esters using lipase biocatalysis. Biphenyl-based building blocks with ester functions represent an important class of precursors that give rise to compounds with anti-infective, anti-inflammatory, and anti-cancer potencies [4,5,6,7,8,9,10], as well as in technical applications, such as in solar cells, where they are used as linkers for dyes [11] and hole transport materials [12], in metal organic frameworks for gas storage [13], and as catalysts [13,14] in lithium ion batteries [15] or rectification devices [16], in nanocomposite thin films for use in organic light emitting diodes (OLED) [17], or even as material in HPLC columns for the isolation of aromatic compounds [18]. Chemoselective hydrolysis and subsequent functionalization of biphenyl ester-based compounds therefore allow the generation of tailored molecules with increased potency and selectivity for their biological targets, improved bioavailability (absorption-distribution-metabolism-excretion-toxicity, ADMET) profiles, or unique magnetic or electronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Dibenz[c,e]azepines constitute an important class of compounds widely employed as chiral or pro-chiral scaffolds for the construction of chiral catalysts for asymmetric synthesis or probes for chiral molecular recognition. In particular, 1,1 -binaphthylazepines have been widely employed as chiral ligands in organometallic catalysis [1][2][3][4][5] and organocatalysis [6][7][8][9][10], while not-atropisomerically stable (i.e., tropos) 1,1 -biphenylazepines have been reported both as structural motifs for the construction of the chiral ligands [9][10][11][12][13][14][15] and as the chiroptical probes for the absolute configuration assignment to the chiral acids [16][17][18][19] and amines [14,20]. In fact, in 1,1 -biphenylazepines the low phenyl-phenyl rotational barrier allows, at room temperature, a free interconversion of the two possible M and P atropisomeric forms.…”
Section: Introductionmentioning
confidence: 99%